Assessment of discrepancies between bottom-up and regional emission inventories in Norwegian urban areas. (April 2017) - López-Aparicio, Susana; Guevara, Marc; Thunis, Philippe; Cuvelier, Kees; Tarrasón, Leonor
Abstract: This study shows the capabilities of a benchmarking system to identify inconsistencies in emission inventories, and to evaluate the reason behind discrepancies as a mean to improve both bottom-up and downscaled emission inventories. Fine scale bottom-up emission inventories for seven urban areas in Norway are compared with three regional emission inventories, EC4MACS, TNO_MACC-II and TNO_MACC-III, downscaled to the same areas. The comparison shows discrepancies in nitrogen oxides (NOx ) and particulate matter (PM2.5 and PM10 ) when evaluating both total and sectorial emissions. The three regional emission inventories underestimate NOx and PM10 traffic emissions by approximately 20–80% and 50–90%, respectively. The main reasons for the underestimation of PM10 emissions from traffic in the regional inventories are related to non-exhaust emissions due to resuspension, which are included in the bottom-up emission inventories but are missing in the official national emissions, and therefore in the downscaled regional inventories. The benchmarking indicates that the most probable reason behind the underestimation of NOx traffic emissions by the regional inventories is the activity data. The fine scale NOx traffic emissions from bottom-up inventories are based on the actual traffic volume at the road link and are much higher than the NOx emissions downscaled from national estimates based on fuel sales and based on population for the urban areas. We have identified important discrepancies in PM2.5 emissions from wood burning for residential heating among all the inventories. These discrepancies are associated with the assumptions made for the allocation of emissions. In the EC4MACs inventory, such assumptions imply high underestimation of PM2.5 emissions from the residential combustion sector in urban areas, which ranges from 40 to 90% compared with the bottom-up inventories. The study shows that in three of the seven Norwegian cities there is need for further improvement of the emission inventories. Highlights: The capability of a benchmarking system to improve emission inventories is shown. The regional emission inventories cannot be readily used in urban areas in Norway. Regional emission inventories underestimate NOx and PM10 urban traffic emissions.